2012
DOI: 10.1261/rna.034777.112
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative diseases: Quantitative predictions of protein–RNA interactions

Abstract: Increasing evidence indicates that RNA plays an active role in a number of neurodegenerative diseases. We recently introduced a theoretical framework, catRAPID, to predict the binding ability of protein and RNA molecules. Here, we use catRAPID to investigate ribonucleoprotein interactions linked to inherited intellectual disability, amyotrophic lateral sclerosis, Creutzfeuld-Jakob, Alzheimer's, and Parkinson's diseases. We specifically focus on (1) RNA interactions with fragile X mental retardation protein FMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 57 publications
5
88
0
Order By: Relevance
“…Indeed, amyloidogenic proteins such as TDP-43 and FMRP (Reactome pathway ‘Amyloids’) have strong propensities to bind to their mRNAs and have been discussed in our previous work (5). …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, amyloidogenic proteins such as TDP-43 and FMRP (Reactome pathway ‘Amyloids’) have strong propensities to bind to their mRNAs and have been discussed in our previous work (5). …”
Section: Resultsmentioning
confidence: 97%
“…Recent studies showed that establishment of aberrant associations or disruption of functional protein–RNA interactions occurs in neurological disorders (5,6). For instance, interaction with RNA favors conversion of alpha-helix rich prion protein PrP C into the pathogenic beta-structure-rich insoluble conformer PrP Sc that propagates in Creutzfeldt–Jakob disease (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, when tested on 12,000 randomly generated RNA associations with proteins extracted from a non-Nucleic Acid-binding dataset [19], ~ 30% of these were predicted to interact with RNA [17]. In a recent study [20], the authors used catRAPID to investigate ribonucleoprotein interactions linked to neurodegenerative diseases. An advantage of the catRAPID algorithm is that it is the only published method that simultaneously predicts the binding sites in both RNA and protein sequences [21].…”
Section: Rna-protein Partner Prediction Methods and Web Serversmentioning
confidence: 99%
“…As discussed above, catRAPID predicts interaction partners based on the interaction propensities of individual residues [17]. In several cases, catRAPID binding site predictions correlate well with experimental results [20,33], but the performance of this method has not been evaluated systematically on benchmark datasets. Therefore, it is difficult to comment on the relative accuracy of this method in predicting interfacial residues in either RNA or protein sequences.…”
Section: Rna-protein Interface Prediction Methodsmentioning
confidence: 99%
“…The cat RAPID algorithm has been previously validated on a number of protein–RNA associations (Agostini et al , 2013; Bellucci et al , 2011; Cirillo, et al , 2013a; Johnson et al , 2012). To evaluate large-scale performances of cat RAPID omics , we used data from recent large-scale experiments.…”
Section: Performancesmentioning
confidence: 99%